Carbon spillover and feedback effects of the middle class in China. (20th December 2021) - Wei, Liyuan; Li, Mengyu; Zuo, Jian; Wang, Xiao; Wang, Zhen; Wang, Ju; Yan, Hua; Liu, Sinuo; Peng, Sha; Hong, Song; Lenzen, Manfred
Abstract: China's middle-class cultivation plan has been put on the agenda. The demographic transformation process is likely to be accompanied by environmental changes. Different income groups have their own characteristics, exerting different degrees of pressure on the environment. Based on a multiregional input-output model, we analyse the spillover-feedback mechanisms among eight regions with special emphasis on household consumption of the middle class in China. Our results show that the middle class, representing two-thirds of the total population, is responsible for 56% of the total carbon spillover, to which Central China and Southwest contributed the most. Central China and developed coastal areas imposed the most spillover while the Northwest bore the most spillover. To satisfy middle-class consumption, Central China is the largest carbon spillover flow net importer in domestic trade, while for the entire household, China's East Coast ranked first. Furthermore, interregional carbon spillover was mostly transferred through the electricity industry, petroleum, chemical and nonmetallic mineral products, metal products, and transport industries, supporting residents' demand for household appliances, living and transport services. Regarding the feedback effect, it is relatively minor. Therefore, we propose regional supply chain adjustment strategies and personal consumption behaviour recommendations in the context of middle-class cultivation in the eight regions of China. Graphical abstract: Image 1 Highlights: Spatial distribution of middle class is explored with population size considered. Carbon spillover of middle class is compared with the case of entire household. Central China and Southwest have the largest potential of middle class cultivation.